PO157 The impact of neuromyelitis optica spectrum disorder on employment. (1st December 2017) - Mutch, Kerry; Linaker, Sam; Whittam, Dan; Hamid, Shahd; Jacob, Anu
Abstract : Background: NMOSD is well known to cause physical disability. However the impact on a patient's life is poorly quantified. One important aspect of this is loss of employment – but no data exists on the proportion of patients affected. Method: A cross-sectional study of 103 patients (84 female, 19 male), median age 53 years (range 18–87) diagnosed aquaporin-4 antibody positive NMOSD, were assessed regarding their employment status. Results: 91/103 patients were of working age when they had their first attack. 72/91 (79%) patients were employed at the time of their first attack. At last follow up 38/72 (53%) were not working; 27/38 (71%) had not worked since their first attack. Of those who continued to work- 34/72 (47%), 22/34 (65%) were in part time work; only 12/34 (35%) patients were in full time work. Conclusion: 60/72 (83%) patients either stopped work or reduced hours following the onset of NMOSD. This has a major impact upon financial, family and social life besides the already known physical effects, highlighting the need for early aggressive treatments.